Developing European Library Services in Changing Times - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
The purpose of this article is to explain what academic and national libraries can do to continue to offer services and facilities at a time of economic difficulties. It identifies a number of methodologies and opportunities that are open to libraries and takes the view that it is never wise to waste a good crisis, because all threats are really opportunities in disguise. The kernel of this paper was delivered at the 10th Anniversary special EISZ Consortium Members’ Meeting on 2 December 2011, in Budapest, Hungary. It builds on an earlier talk delivered in Thessaloniki, Greece, on 14–15 November 2011 at the 20th Pan-Hellenic Academic Libraries Conference, entitled ‘Academic Libraries and Financial Crisis: Strategies for Survival’. Both these presentations are available in UCL Discovery. This article draws on themes used in both presentations, and introduces a new one on the topic of copyright reform. The article looks at the initial economic context for European research libraries and then examines ways in which libraries can tackle the threats which the current financial crisis poses. Joint procurement is one way in which libraries can achieve value for money, and the paper examines the role of JISC Collections in the UK. Innovation through collaboration and shared services are also ways in which libraries can innovate/make savings in a cost-effective way by sharing the burden of costs around the partnership. The paper gives two examples: one which is now well established, the DART-Europe portal for Open Access e-theses; and one which is in the early stages of being discussed — a cloud-based solution for true collaborative cataloguing amongst the UK’s research and national libraries. The European Research Area (ERA) and the contributions that libraries can make to this infrastructure through innovative EU project funding are analysed in some detail by looking at LIBER’s EU project portfolio. Finally, change and growth can come through changes to legal frameworks, and the paper looks at the Hargreaves review of copyright frameworks in the UK and the launch of the new library-based EU lobbying group for copyright reform, Information Sans Frontières (ISF).